T&TUTA Newsletter: No.2 - Mark, Paula; Farfan, Gerard; Seepersad, Frank B.; Taylor, Harold M. (Trinidad and Tobago Unified Teachers' Association (TTUTA), 1980)
This issue of the Newsletter highlights: a) plans for the future by 1st Vice President Dr. Paula Mark in an article "Needs and Priorities: A Glimpse of the Future" for the professional and cultural advancement of our teachers. (b) an up to date account of the situation re. the amendments to the Education Act by 2nd Vice President. Fr. Gerard Farfan.
Keywords: Trinidad and Tobago Unified Teachers' Association